2000
DOI: 10.4049/jimmunol.165.1.539
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Administration of Cytosine-Phosphorothiolated Guanine-Containing Oligonucleotides Together with Peptide/Protein Immunization Results in Enhanced CTL Responses with Anti-Tumor Activity

Abstract: The development of therapeutic anti-cancer vaccines designed to elicit CTL responses with anti-tumor activity has become a reality thanks to the identification of several tumor-associated Ags and their corresponding peptide T cell epitopes. However, peptide-based vaccines, in general, fail to elicit sufficiently strong CTL responses capable of producing therapeutic anti-tumor effects (i.e., prolongation of survival, tumor reduction). Here we report that repeated administration of synthetic oligonucleotides con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
2
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 45 publications
6
90
2
1
Order By: Relevance
“…Although some studies have showed induction of MUC1-specific antibodies in animal models and cancer patients [Reviewed in 10], our studies demonstrating the induction of CTL responses corroborate numerous reports in which CpG-ODN alone [33,37,48,49] or in combination with GM-CSF [24] were used as biologic adjuvants in peptide vaccines. A likely explanation of our results is that MHC class I-restricted MUC1 peptides which stimulate CD8 + T cells are acting in concert with CpG-ODN and GM-CSF in the vaccine cocktail to promote strong T H1 type responses resulting in the generation of efficient CTL anti-tumor responses [24,33,37,48,50]. In addition, inclusion of CpG-ODN in the vaccination cocktail in our study did not cause destruction of the lymphoid follicles or prevent isotype switching in treated mice (data not shown) as was reported by Heikenwalder, et al [51].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although some studies have showed induction of MUC1-specific antibodies in animal models and cancer patients [Reviewed in 10], our studies demonstrating the induction of CTL responses corroborate numerous reports in which CpG-ODN alone [33,37,48,49] or in combination with GM-CSF [24] were used as biologic adjuvants in peptide vaccines. A likely explanation of our results is that MHC class I-restricted MUC1 peptides which stimulate CD8 + T cells are acting in concert with CpG-ODN and GM-CSF in the vaccine cocktail to promote strong T H1 type responses resulting in the generation of efficient CTL anti-tumor responses [24,33,37,48,50]. In addition, inclusion of CpG-ODN in the vaccination cocktail in our study did not cause destruction of the lymphoid follicles or prevent isotype switching in treated mice (data not shown) as was reported by Heikenwalder, et al [51].…”
Section: Discussionsupporting
confidence: 88%
“…The MHC class I peptides confer MUC1 specificity leading to the induction of CTL-mediated anti-tumor responses; the Hepatitis B core antigen-derived MHC class II pan T helper peptide was included to boost CD8 + anti-tumor responses [30,31]; CpG-ODN was included to promote DC activation via its interaction with Toll-like receptor (TLR)-9 [32,33] to enhance CTL responses, expansion and survival [33][34][35][36][37]. GM-CSF promotes antigen presentation and DC recruitment to vaccine sites [38][39][40][41] and is commonly used as a biological adjuvant in preclinical and clinical immunotherapy studies [42,43].…”
Section: Effect Of Peptide Vaccination On Adenoma Formation In Muc1tmentioning
confidence: 99%
“…Indeed, as seen in the treated mice (Fig. 6) and reported by others [12,29], the repeated injection of very stable phosphorothioate CpG DNA oligonucleotides leads to uncontrolled immune stimulation (evidenced by splenomegaly and potentially leading to autoimmunity). On the contrary, stabilized RNA that do not induce the proliferation of B cells [18] and that have a half-life of approximately 110 h in serum [19] are naturally cleared with reliable and reproducible kinetics from the site of injection, thereby offering a controllable therapeutic window.…”
Section: Discussionsupporting
confidence: 77%
“…TRP-2 is a non-mutated protein that is expressed by normal melanocytes in C57BL/6 mice [24]; therefore, it is subject to self-tolerance. Amino acids 257−264 of the ovalbumin protein (OVA 257−264 ) form an immunogenic epitope that is presented by H-2 K b [11]. Amino acids 366−374 of the influenza A nucleoprotein (NP 366−374 ) [2] and amino acids 49−57 of the human papillomavirus E7 protein (E7 49−57 ) [25] form immunogenic epitopes presented by H-2 D b .…”
Section: Methodsmentioning
confidence: 99%